PENINGKATAN KUALITAS PEMBELAJARAN FISIKA PADA KONSEP BESARAN DAN SATUAN MELALUI RANCANGAN LESSON STUDY (SISWA KELAS X SEMESTER GASAL SMA NEGERI 1 CEPER KABUPATEN KLATEN) - SUMADI , SUMADI (2011)
This study is conducted using Classroom Action Research design with lesson study framework. Classroom Action Research is a precision of activity which is intended to conduct and occur in a class. Lesson study s conducted collaboratively with other teacher in three cycles there are planning, implementing, and continuous reflection. The subject of the study is the odd semester students of XA SMA Negeri 1 Ceper Kabupaten Klaten 2009/2010 academic year. The methods of collecting data are participative observation, document, students' observation sheet, and test. The data are analyzed through data reduction, data display, and draw conclusion. The study shows two results. First, the Physics learning process quality in the concept of magnitude and unit with the discussion method and giving tasks using lesson study framework always has improvement from pre-cycle through cycle III. The students' learning concentration is more improved, when it is conducted group discussion, the students are more active. The students' feel interested in the learning process using complete tools and LCD media displaying power point and animation. Secondly, the implementation of learning through lesson study is proved to be very effective in improving the mastery of magnitude and unit concept of the even semester students of X year of SMA Negeri 1 Ceper. It is proved by the improvement of students' average score in pre-cycle through cycle III. From pre-cycle to cycle I the improvement is 15,64%. From cycle I to cycle II, the improvement is 25.47%. From cycle II to cycle III, the improvement is 12,13%.